Androgen levels of reproductive competitors in a co-operatively breeding cichlid - Oliveira, R. F. (2014)
Androgen levels of family groups of Neolamprologus pulcher were assessed using non-invasive methods. There were no significant differences in the excretion rates neither of testosterone nor of 11-ketotestosterone between territorial and helper males.